2021
DOI: 10.1186/s40792-020-01089-0
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence after ESD curative resection for early gastric cancer

Abstract: Background Endoscopic submucosal dissection (ESD) is gaining ground as a minimally invasive treatment for early gastric cancer (EGC) that has a negligible risk of lymph node metastasis. According to the 5th edition of Japanese gastric cancer treatment guidelines, annual or biannual follow-up with endoscopy is recommended, but follow-up with abdominal ultrasonography or computed tomography (CT) for surveillance of metastases is not recommended after the eCuraA resection. However, we experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…There have been no reported instances of regional lymph node recurrence in the absence of intragastric lesions after curative endoscopic resection in patients meeting the absolute indications, such as the case in this report. However, the case with the closest similarity was that by Kamiya et al, [ 7 ] which presented with extragastric recurrence without intragastric lesions, after curative endoscopic resection of well-differentiated intramucosal early gastric cancer having a size of 30 mm without evidence of ulceration and lymphovascular invasion. The findings of this case are consistent with the findings of Lee et al [ 6 ] who reported 3 cases of regional lymph node recurrence without intragastric lesions from among 1302 patients who underwent curative resection under the expanded indications for endoscopic resection.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…There have been no reported instances of regional lymph node recurrence in the absence of intragastric lesions after curative endoscopic resection in patients meeting the absolute indications, such as the case in this report. However, the case with the closest similarity was that by Kamiya et al, [ 7 ] which presented with extragastric recurrence without intragastric lesions, after curative endoscopic resection of well-differentiated intramucosal early gastric cancer having a size of 30 mm without evidence of ulceration and lymphovascular invasion. The findings of this case are consistent with the findings of Lee et al [ 6 ] who reported 3 cases of regional lymph node recurrence without intragastric lesions from among 1302 patients who underwent curative resection under the expanded indications for endoscopic resection.…”
Section: Discussionmentioning
confidence: 96%
“…[ 4 , 5 ] Extragastric recurrence in the absence of intragastric lesions has been reported in the past for cases that met the criteria of the expanded indications of endoscopic resection. [ 6 , 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, cases of lymph node metastasis recurrence despite the diagnosis of R0 resection of intramucosal carcinoma after ESD has been reported. This suggests that submucosal invasion existed in the section where H&E slides were not made 16 , 17 . WTI and WBI with micro-CT scans can observe findings that cannot be confirmed by conventional pathology slides and may lead to a more accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, many global gastric cancer treatment guidelines recommend endoscopic surgery as the preferred treatment strategy for early gastric cancer. However, despite the effectiveness of ESD, its associated high rate of heterochronic recurrence needs to be addressed [6]. Studies have shown that recurrence usually occurs near the original tumor site, highlighting the need to assess and predict possible risk factors for recurrence [7][8][9].…”
Section: Introductionmentioning
confidence: 99%